2016
DOI: 10.1186/s13053-016-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in neuropsychological and behavioral parameters and brain structure in patients with familial adenomatous polyposis: a sibling-paired study

Abstract: BackgroundFamilial adenomatous polyposis (FAP) is an autosomal dominant hereditary colon cancer syndrome caused by mutations in adenomatous polyposis coli (APC) with both colonic and extra-colonic manifestations. Case reports have noted an association with FAP and intellectual disability and animal studies have shown that APC is implicated in neural development and function, but no studies have investigated neuropsychological, behavioral, or structural brain characteristics of patients with FAP.MethodsWe under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Interestingly, there were no group differences noted on the adult selfratings (BRIEF questionnaire) of executive functions, perhaps secondary to self-perceptions not recognizing the subtle differences that might be present when compared to their peers. Original observations describing intellectual disabilities among individuals with FAP were limited to case reports [4,5,7]. Patients with FAP were shown to perform lower on test of intellectual capacity, particularly on verbal tasks, when compared to patients with ulcerative colitis [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there were no group differences noted on the adult selfratings (BRIEF questionnaire) of executive functions, perhaps secondary to self-perceptions not recognizing the subtle differences that might be present when compared to their peers. Original observations describing intellectual disabilities among individuals with FAP were limited to case reports [4,5,7]. Patients with FAP were shown to perform lower on test of intellectual capacity, particularly on verbal tasks, when compared to patients with ulcerative colitis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these known linkages few empirical findings examining the relationship between the expression of the APC protein and neurocognitive and behavioral functioning in individuals with APC mutations exist [4][5][6][7]. To date, animal studies have associated APC dysfunction with altered synaptic function in APC cKO mice, which plays a critical role in learning and memory [8].…”
Section: Introductionmentioning
confidence: 99%
“…A 2010 study by researchers at the Cleveland Clinic reported that though FAP patients have IQs parallel with the general population, hearing/language-dependent verbal scores were significantly lower than those without the mutation ( O'Malley et al, 2010 ). Preliminary data in a small sample, sibling-paired pilot study suggested that siblings who are FAP positive are more likely to suffer from behavioral and emotional problems than their healthy siblings ( Azofra et al, 2016 ), and a prior study reported a high incidence of formal psychiatric diagnoses (especially anxiety diagnoses) in FAP adolescents ( Gjone et al, 2011 ). The most recent investigation of neurocognitive function of FAP patients identified and characterized robust deficits in several cognitive measures (particularly long term retrieval and cognitive fluency), suggesting that APC protein plays a critical role in cognition ( Cruz-Correa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 92%
“…A 2010 study by researchers at the Cleveland Clinic reported that though FAP patients have IQs parallel with the general population, hearing/language-dependent verbal scores were significantly lower than those without the mutation (O’Malley et al, 2010). Preliminary data in a small sample, sibling-paired pilot study suggested that siblings who are FAP positive are more likely to suffer from behavioral and emotional problems than their healthy siblings (Azofra et al, 2016), and a prior study reported a high incidence of formal psychiatric diagnoses (especially anxiety diagnoses) in FAP adolescents (Gjone, Diseth, Fausa, Nøvik, & Heiberg, 2011). The most recent investigation of neurocognitive function of FAP patients identified and characterized robust deficits in several cognitive measures (particularly long term retrieval and cognitive fluency), suggesting that APC protein plays a critical role in cognition (M. R. Cruz-Correa et al, 2020).…”
Section: Introductionmentioning
confidence: 92%